Risk reduction partnerships in railway transport infrastructure in an alpine environment. (February 2019) - Otto, Antje; Kellermann, Patric; Thieken, Annegret H.; Máñez Costa, Maria; Carmona, Maria; Bubeck, Philip
Abstract: The transport sector is crucial for the functioning of modern societies and their economic welfares. However, it is vulnerable to natural hazards since damage and disturbances appear recurrently. Risk management of transport infrastructure is a complex task that usually involves various stakeholders from the public and private sector. Related scientific knowledge, however, is limited so far. Therefore, this paper presents detailed information on the risk management of the Austrian railway operator gathered through literature studies, in interviews, meetings and workshops. The findings reveal three decision making levels of risk reduction: 1) a superordinate level for the negotiation of frameworks and guidelines, 2) a regional to local level for the planning and implementation of structural measures and 3) a regional to local level for non-structural risk reduction measures and emergency management. On each of these levels, multi-sectoral partnerships exist that aim at reducing the risk to railway infrastructure. Chosen partnerships are evaluated applying the Capital Approach Framework and some collaborations are analyzed considering the flood and landslide events in June 2013. The evaluation reveals that the risk management of the railway operator and its partners has been successful, but there is still potential for enhancement. Difficulties are seen for instance in obtaining continuity of employees and organizational structures which can affect personal contacts and mutual trust and might hamper sharing data and experiences. Altogether, the case reveals the importance of multi-sectoral partnerships that are seen as a crucial element of risk management in the Sendai Framework for Disaster Risk Reduction 2015–2030.